Selenium and lung cancer: a systematic review and meta analysis. - Heidi Fritz; Deborah Kennedy; Dean Fergusson; Rochelle Fernandes; Kieran Cooley; Andrew Seely; Stephen Sagar; Raimond Wong; Dugald Seely (PLoS ONE)
Background Selenium is a natural health product widely used in the treatment and prevention of lung cancers, but large chemoprevention trials have yielded conflicting results. We conducted a systematic review of selenium for lung cancers, and assessed potential interactions with conventional therapies. Methods and findings Two independent reviewers searched six databases from inception to March 2009 for evidence pertaining to the safety and efficacy of selenium for lung cancers. Pubmed and EMBASE were searched to October 2009 for evidence on interactions with chemo- or radiation-therapy. In the efficacy analysis there were nine reports of five RCTs and two biomarker-based studies, 29 reports of 26 observational studies, and 41 preclinical studies. Fifteen human studies, one case report, and 36 preclinical studies were included in the interactions analysis. Based on available evidence, there appears to be a different chemopreventive effect dependent on baseline selenium status, such that selenium supplementation may reduce risk of lung cancers in populations with lower baseline selenium status (serum<106 ng/mL), but increase risk of lung cancers in those with higher selenium (≥ 121.6 ng/mL). Pooling data from two trials yielded no impact to odds of lung cancer, OR 0.93 (95% confidence interval 0.61-1.43); other cancers that were the primary endpoints of these trials, OR 1.51 (95%CI 0.70-3.24); and all-cause-death, OR 0.93 (95%CI 0.79-1.10). In the treatment of lung cancers, selenium may reduce cisplatin-induced nephrotoxicity and side effects associated with radiation therapy. Conclusions Selenium may be effective for lung cancer prevention among individuals with lower selenium status, but at present should not be used as a general strategy for lung cancer prevention. Although promising, more evidence on the ability of selenium to reduce cisplatin and radiation therapy toxicity is required to ensure that therapeutic efficacy is maintained before any broad clinical recommendations can be made in this context.